DESIGN AND EVALUATION OF BILAYER TABLETS OF GLIMEPIRIDE AND METFORMIN HYDROCHLORIDE WITH COMBINATION OF HYDROPHILIC AND HYDROPHOBIC POLYMERS BY HOT MELT EXTRUSION - wagh, Kalpesh s; KALE, SACHIN S; Mali, Kamlesh D; Patil, Satish K; Baviskar, Dheeraj T (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The aim of present study was to design and evaluate bilayered tablets of Metformin Hydrochloride as sustained release and Glimepiride as immediate release form for the treatment of diabetes mellitus. Immediate release layer of glimepiride prepared using different super disintegrants. Prepared tablets were evaluated for routine Pharmacopoeial evaluation tests. The use of a hydrophobic carrier along with a hydrophilic polymer effectively controls the initial rapid release of a highly water soluble drug like Metformin HCl. Sustained release granules were prepared by hot melt extrusion technique. Results confirmed the complete and rapid release of immediate release layer while sustaining effect for sustained layer observed for 10 hours. The drug release data subjected to various mathematical models to determine the kinetics of SR layer using regression coefficient. The best fit model was Korsemeyer-peppas indicating non-fickian transport. Stability studies and FT-IR studies indicated absence of drug-polymer interaction. The current study successfully achieved the design and development of bilayer tablet formulation. Keywords: Sustained release, immediate release, Hot melt extrusion, Eudragit RSPO, PEG 6000, bilayer.Â